2012
DOI: 10.1007/s13280-012-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Non-Point Source Pollution in China: Causes and Mitigation Measures

Abstract: Non-point source (NPS) pollution has been increasingly serious in China since the 1990s. The increases of agricultural NPS pollution in China is evaluated for the period 2000-2008 by surveying the literature on water and soil pollution from fertilizers and pesticides, and assessing the surplus nitrogen balance within provinces. The main causes for NPS pollution were excessive inputs of nitrogen fertilizer and pesticides, which were partly the result of the inadequate agricultural extension services and the rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
199
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(238 citation statements)
references
References 18 publications
1
199
0
4
Order By: Relevance
“…There is no doubt that chemical fertilizers are playing a vital role to meet the nutrient requirement of crops and thereby increase their production. However, in the present scenario the non-judicious use of fertilizers is posing both economic and ecological problems which are often difficult to face, particularly in developing countries (Sutton et al 2011;Sun et al 2012). Widespread nutrient deficiency in soils, disturbed soil reaction, development of nutrient imbalance in plant, increased susceptibility of plants to diseases, reduced soil organic matter, lesser occurrence of beneficial soil microorganism and increased environmental pollution as well as human health hazards are the key problems associated with indiscriminate and over use of synthetic fertilizers (Das et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that chemical fertilizers are playing a vital role to meet the nutrient requirement of crops and thereby increase their production. However, in the present scenario the non-judicious use of fertilizers is posing both economic and ecological problems which are often difficult to face, particularly in developing countries (Sutton et al 2011;Sun et al 2012). Widespread nutrient deficiency in soils, disturbed soil reaction, development of nutrient imbalance in plant, increased susceptibility of plants to diseases, reduced soil organic matter, lesser occurrence of beneficial soil microorganism and increased environmental pollution as well as human health hazards are the key problems associated with indiscriminate and over use of synthetic fertilizers (Das et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the environmental problems in the rural areas have been becoming more severe, and a lot of new environmental problems emerged in large numbers (Sun et al, 2012). For example, according to the National Soil Pollution Census Bulletin (2014) issued by the Ministry of Environmental Protection (MEP) and the Ministry of Land and Resources (MLR), the national soil environmental conditions overall are not optimistic and the over limit rate is 16.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural nonpoint-source pollution is an important factor for water pollution (Sun et al, 2012;Zhu and Pu, 2004 primitive farming methods in China, massive amounts of nitrogen and phosphorus enter the ground and surface water bodies, resulting in eutrophication and an inhospitable environment for the survival of aquatic life (He et al, 1998;Ongley et al, 2010). Studies have found (Mao et al, 2006) that Beitang has a significant impact on the production and migration processes of nonpoint source pollutants.…”
Section: Introductionmentioning
confidence: 99%